RFE Confidential Reports on Poland
This series consists of limited distribution reports (analyses, studies, and interpretations), some of which were, in their time, considered strictly confidential. They had been produced by RFE’s regional News Bureaus (Berlin, Brussels, London, New York, Paris, Rome, Stockholm, Vienna). In some of the reports sensitive issues are described: (re)defection, surveillance of foreign visitors, and the general state of spirits and morale in Poland. In 1971 RFE has decided to anonymize the cities where the reports had been produced, so they bear alphabetical and numeric codes instead of the names of cities. Accruals not expected